2021
DOI: 10.1186/s12940-021-00803-1
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of 25-hydroxyvitamin D and secondhand smoke exposure on hypertension in non-smoking women of childbearing age: NHANES 2007-2014

Abstract: Background Vitamin D deficiency (VDD) may increase the risk of hypertension in women of childbearing age, who may be exposed to secondhand smoke (SHS) simultaneously. Till now, few studies have investigated the joint effects of VDD and SHS on hypertension in this population. We evaluated whether exposure to SHS modified the association between VDD and hypertension. Methods Data from National Health and Nutrition Examination Surveys (NHANES) 2007-20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…25-hydroxyvitamin D [25(OH)D], the main form of circulating vitamin D, is widely applied as an indicator of vitamin D status. It is now well demonstrated that vitamin D also plays a role in many extra-skeletal health issues [ 2 ], such as metabolic syndrome (MetS) [ 3 , 4 ], type 2 diabetes mellitus (T2DM) [ 5 ], abdominal obesity [ 6 , 7 ], hypertension [ 8 , 9 ], and dyslipidemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…25-hydroxyvitamin D [25(OH)D], the main form of circulating vitamin D, is widely applied as an indicator of vitamin D status. It is now well demonstrated that vitamin D also plays a role in many extra-skeletal health issues [ 2 ], such as metabolic syndrome (MetS) [ 3 , 4 ], type 2 diabetes mellitus (T2DM) [ 5 ], abdominal obesity [ 6 , 7 ], hypertension [ 8 , 9 ], and dyslipidemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence showing that vitamin D deficiency can trigger negative outcomes for both the mother and child, including hypertension in women of childbearing age [ 9 ], gestational diabetes [ 10 ] and negative adverse perinatal outcomes [ 11 ] such as first trimester miscarriages [ 12 ] has resulted in a growing public health concern at primary care level and the need of public policies at the national level. Vitamin D deficiency has also been associated with some extra-skeletal damages, such as osteoporosis, chronic musculoskeletal pain, muscle weakness, and an increased risk of falling [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency has also been associated with some extra-skeletal damages, such as osteoporosis, chronic musculoskeletal pain, muscle weakness, and an increased risk of falling [ 13 , 14 , 15 , 16 ]. The negative adverse perinatal outcomes [ 17 ] include impairment of anthropometric measurements of the neonate such as birth weight, length, and head circumference [ 18 ] in addition to a higher risk of premature rupture of membranes [ 10 ] and miscarriage [ 19 ]. At birth, it can be related to infantile eczema, nutritional rickets, severe hypocalcemia, and other orthopedic complications in neonates and children [ 20 ].Therefore, vitamin D deficiency in combination with periodontal disease has been associated with preterm and low birth weight [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another prospective study we conducted before, we determined that vitamin D levels were lower in preeclamptic pregnant women [ 6 ]. According to an article published in 2021, the findings suggested that vitamin D deficiency and passive smoking during pregnancy might have a synergistic impact on gestational hypertension [ 12 ]. Thus, it should be kept in mind that vitamin D deficiency and smoking may be important interrelated factors for hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 99%